UPAYA GURU PAI DALAM MENINGKATKAN KOMPETENSI KOGNITIF DAN KEPRIBADIAN SISWA DI MTs NEGERI 1 BONGKUDAI - Prasetio Rumondor; Nailil Maslukiyah (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2019)
In the world of formal education, the teacher is an important part of the success of students. In this country education serves to educate the nation which aims to develop the potential of students while at the same time becoming a man of faith and devotion to God, mastering science and technology as stated in Law no. 20 of 2003. In this study using qualitative research methods. The results of the study show that the efforts made by PAI teachers in improving students' cognitive and personality competencies include initiatives to create learning forums outside school hours, advise, and direct students to study in the library. Then, the average cognitive ability of students is good. And, in terms of personality students have good personalities such as honesty, politeness, and exemplary it's just not prominent. In order for students to have good personalities, the teacher invites students to pray in the congregation at the mosque, provide knowledge and understanding such as advice and if wrong then given a law that educates, tells the stories of prophets, friends and scholars. From the efforts made by the teacher, there are factors that support such as the teacher having competence, the convenient location of the school and the school infrastructure facilities are adequate while the obstacles are the environment, student association, family problems, and the surrounding community, as well as the current technology.